Holder Pasteurization: Comparison of Water-Bath and Dry-Tempering Devices - Müller, Katharina; Toll, Luisa J.; Manzardo, Olimpia A.; Baumgartner, Jana; Nickel, Erika; Wenzel, Folker; Klotz, Daniel (Frontiers in Pediatrics, 2022)
Background Human milk (HM) for premature infants is frequently Holder pasteurised (heated at 62±0.5°C for 30 min) despite its detrimental effects on heat-sensitive milk components. This tolerated compromise ensures HM’s microbial safety while less detrimental methods like short-time HM treatments (HTST) are still being evaluated. Dry-tempering devices (DT-HoP) were recently introduced in clinical practice due to hygienic concerns about water-based Holder pasteurisers (WB-HoP). Evidence on the impact of such dry-tempering devices on HM quality is lacking. The aim of this study was to compare protein retention rates after DT-HoP, WB-HoP and HTST. Methods We colorimetrically determined alkaline phosphatase activity (ALP), concentrations of secretory immunoglobulin A (sIgA), and lactoferrin (LF) before and after DT-HoP, WB-HoP and HTST. Results ALP was below the detection limit after HoP, but retained 52.8±13% activity after HTST (p<0.01). Secretory IgA (WB-HoP=73.2±13.5% versus DT-HoP=57±14%, p=0.0018) and LF retention (WB-HoP=47±40% versus DT-HoP=25±8%, p=0.07) differed between the two HoP modes. Again, retention was better maintained after HTST compared to HoP (80.4±23% sIgA and 70±42% LF concentration, all p<0.01). Conclusion Dry-tempering milk lowers even further the quality of HM when performing HoP compared to water-bath pasteurisation, while HTST warrants continued evaluation for clinical application.